OLD LOCATIONS FOR NEW ECONOMIES: CASE STUDY OF CITY OF SKOPJE - Mickovski, Goran; Velevski, Slobodan; Mano Velevska, Marija (STRAND - Sustainable Urban Society Association Belgrade, Serbia, 2019)
Rapid urbanization and forced industrialization during socialism, lead to enormous extension of urban territory and unrestricted and irrational utilization of locations for industrial production. The end of socialist system caused multiple processes of transformation in the city, where one of the most expressed was the deindustrialization. It produced vast areas and numerous locations to be permanently abandoned or insufficiently utilized. This paper examines and presents the opportunities for reuse of abandoned or unused industrial locations and buildings within the urban territory of the city of Skopje. The industrial locations and buildings had became valuable and attractive urban assets with potential for reuse. In addition, both represent important part of city history, where the process of industrialization contributed tremendously to social, economic and cultural development of Skopje. Their prospect use shall create link with social-economic background, culture and architecture of certain era and continuity with the past. We represent the standing that abandoned industrial locations and buildings in Skopje should be used by creative and non-material production industries. The creative economy as generator of growth can be treated as crucial sector for innovation, knowledge transfer, economic diversification, pool of highly skilled educated employees necessary to achieve sustainable development goals for the city of future.
Keywords: industrial location; deindustrialization; creative industry; non-material production industry